Association of periodontitis with increased colonization by Prevotella nigrescens. Issue 1 (6th July 2012) - Stingu, Catalina‐Suzana; Schaumann, Reiner; Jentsch, Holger; Eschrich, Klaus; Brosteanu, Oana; Rodloff, Arne C.
Abstract Aim To estimate differences in the prevalence of Prevotella intermedia and Prevotella nigrescens in the subgingival plaque of patients with periodontitis (including aggressive and advanced chronic periodontitis) compared to healthy controls, and to search for significant associations with clinical status. Methods Sixteen patients and 16 healthy controls were enrolled in this study. Interproximal plaque index, oral hygiene index, gingival index, bleeding on probing, probing depth, and clinical attachment level were recorded. Samples of subgingival plaque were taken with paper points from four teeth of each individual and immediately plated on appropriate supplemented Columbia agar. Black pigmented colonies were identified with the Rapid ID32 A system, and further differentiated using matrix‐assisted laser desorption ionization–time of flight mass spectrometry. For the statistical analysis, chi‐squared test and the Mann–Whitney U‐test were used. Results Prevotella nigrescens was isolated from 10 patients and three controls, while P. intermedia was isolated from only two patients. P. nigrescens was found more frequently in the subgingival plaque of patients (P = 0.029), and was significantly associated with high values of clinical indices (P ≤ 0.025). Significant differences for P. intermedia were not found. Conclusions Periodontitis seems to be associated with increased coloniza‐tion with P. nigrescens. Whether or not it is a major pathogen needs to be determined.